THE INFLUENCE OF PROMOTION STRATEGIES THROUGH SOCIAL MEDIA AND WORD OF MOUTH MARKETING ON SCHOOL SELECTION DECISIONS (CASE STUDY AT SMK MUHAMMADIYAH PARAKAN) - Wijaya, Muhamad Restu (IJOSMAS, 2021)
The purpose of this study was to determine the effect of promotional strategies through social media on school selection decisions, the effect of word of mouth marketing on school selection decisions, and the effect of promotional strategies through social media and word of mouth marketing together on school selection decisions at SMK Muhammadiyah Parakan. . The research was conducted at SMK Muhammadiyah Parakan which is located at Jalan Pamulang 2 Benda Barat 11, Ritan Complex, Parakan Village RT 03/09 Pondok Benda Village - South Tangerang City. This research model uses quantitative research methods. This research was analyzed using Multiple Linear Regression analysis with SPSS program. The population as well as the sample in this study were all students of class X SMK Muhammadiyah Parakan in 2020, totaling 44 people. Methods of data analysis using data quality test, classical assumption test and hypothesis testing. Based on the results of the study, there is a positive influence between promotion through social media (X1) on school selection decisions (Y). This is evidenced by the t-count of 6.386 with a significance value of 0.000 less than 0.05. And the coefficient of determination or contribution of influence is 0.702 or 70.2% while the remaining 29.8% is influenced by other factors. There is a positive influence between word of mouth marketing (X2) on school selection decisions (Y). This is evidenced by the t-count of 6.323 with a significance value of 0.000 less than 0.05. And the coefficient of determination or contribution of influence is 0.698 or 69.8% while the remaining 30.2% is influenced by other factors. There is a positive influence between promotion through social media (X1) and word of mouth marketing (X2) on school selection decisions (Y). This is evidenced by the calculated F of 26,657 with a significance value of 0.000 less than 0.05. And the coefficient of determination or contribution of influence is 75.2% while the remaining 24.8% is influenced by other factors.